ROOT DYNAMICS OF AEROBIC RICE UNDER ORGANIC NUTRIENT SOURCES AND INORGANIC NUTRIENT LEVELS - P. SURENDRABABU; M. YAKADRI, J. S. SUDHA RANI, B. SREEDEVI, K. P. VANI, M. VENKATA RAMANA, P. C. LATHA (The Journal of Research, PJTSAU, 2023)
A field experiment was conducted on root dynamics of aerobic rice under organic sources and inorganic nutrient levels during kharif, 2017and 2018. The experiment was laid out in split plot design with four organic sources of nutrients as main plots viz: Neem leaf manure (@ 6 t ha-1),Vermicompost (@ 2 t ha-1), Goat manure (@ 5 t ha-1) and Microbial consortia (seed treatment @ 4g kg-1 + soil application @4 kg ha-1) and four subplots with graded dosesof fertilizers viz; Control, 50 % RDF, 75 % RDF and 100 % RDF (120-60-40).The study revealed that various nutrient sources and inorganic nutrient levels exerted a remarkable effect on root traits viz; root length, root biomass, root volume and while root-shoot ratio was not impacted significantly by nutrient sources. Application of vermicompost (@ 2 t ha-1) or goat manure (@ 5 t ha-1) resulted in higher root length, root biomass and root volume. Inorganic nutrient levels of 100% RDF (120-60-40) produced higher root length, root biomass, root volume and root-shoot ratio than lower doses.